In Vitro Anti-cancer Activities of Chinese Chaste Tree and Indian Turnsole against Pc3 and Hela Cell Lines - Jain, Sourabh (International Journal of Pharmaceutical & Biological Archive, 2023)
Natural products discovered from medicinal plants have played an important role in the treatment of cancer. The present study points to the potential anticancer activity of chloroform and ethanol extract of Vitex negundo and Heliotropium indicum. Further studies to characterize the active principles and elucidate the mechanism of the action of ethanol and chloroform extract are in progress. Hence, these plant extracts may have clinical and therapeutic proposition in the most life threaten disease like cancer and further studies are required to investigate these plant samples as antineoplastic agents.